2003
DOI: 10.1093/hmg/ddg328
|View full text |Cite
|
Sign up to set email alerts
|

RING finger 1 mutations in Parkin produce altered localization of the protein

Abstract: The Parkin gene (PRKN) encodes an E3 protein-ubiquitin ligase for which loss of function is associated with autosomal-recessive juvenile (<20 years) and early-onset Parkinsonism (<45 years). Although detailed pathological reports are scarce, brains from patients with homozygous exonic deletions demonstrate neuronal loss in the substantia nigra, albeit without the Lewy body pathology characteristic of idiopathic Parkinson's disease. However, there are rare descriptions of more florid pathology, including Lewy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
103
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(116 citation statements)
references
References 44 publications
10
103
0
1
Order By: Relevance
“…24 It was reported to produce an unusual distribution of the Parkin protein, with large cytoplasmic and nuclear inclusions. 26 The rate of PINK1 mutations in EOP is currently largely unknown, but estimated to be almost as high as the frequency of Parkin mutations based on a single study that reported seven PINK1 mutation carriers among 100 EOP patients, including five with heterozygous mutations. 10 Taking a different approach, a second investigation evaluated the role of PINK1 mutations in a set of 39 families with autosomal recessively inherited EOP and detected homozygous PINK1 mutations in six out of the eight EOP families that were shown to be linked to the PINK1 chromosomal region.…”
Section: Discussionmentioning
confidence: 99%
“…24 It was reported to produce an unusual distribution of the Parkin protein, with large cytoplasmic and nuclear inclusions. 26 The rate of PINK1 mutations in EOP is currently largely unknown, but estimated to be almost as high as the frequency of Parkin mutations based on a single study that reported seven PINK1 mutation carriers among 100 EOP patients, including five with heterozygous mutations. 10 Taking a different approach, a second investigation evaluated the role of PINK1 mutations in a set of 39 families with autosomal recessively inherited EOP and detected homozygous PINK1 mutations in six out of the eight EOP families that were shown to be linked to the PINK1 chromosomal region.…”
Section: Discussionmentioning
confidence: 99%
“…Third, although some proposed substrates such as Pael-R accumulate in postmortem AR-JP brains (Imai et al, 2001;Shimura et al, 2001), parkin knock-out mice do not show elevated steady-state concentrations of other substrates such as CDCrel-1 and synphilin-1 (Von Coelln et al, 2004). Fourth, many parkin mutations show altered solubility and form aggresome-like structures in transfected cells (Ardley et al, 2003;Cookson et al, 2003;Gu et al, 2003;Muqit et al, 2004;Henn et al, 2005;Wang et al, 2005a), thereby conferring potentially toxic properties.…”
Section: Relationship Between Parkin Mutations and Cell Deathmentioning
confidence: 99%
“…Perhaps those types of mutations may contribute to explain the effect of some heterozygous mutations in humans. In fact, missense mutations in both RING fingers of parkin that dramatically alter its cellular localization and generate both cytoplasmic and nuclear inclusions in neuronal cell culture assays have been recently described (12,27).…”
Section: The Rbr Domainmentioning
confidence: 99%